A comparative study of the conduction velocity of motor and sensory fibres of ulnar and median nerves among leprosy patients and normal subjects - Saha, Ishita; Bhattacharyya, Sujoy P.; Bandyopadhyay, Debabrata (International Journal of Research in Medical Sciences, 2020)
Background: Leprosy and the associated scourge have affected humanity for thousands of years. One of the most debilitating consequences of leprosy is peripheral neuropathy. Nerve Conduction Velocity study provides us with a non-invasive modality to assess peripheral nerve involvement in leprosy. Methods: With this in mind, a cross-sectional observational study was conducted including 30 leprosy patients as "Cases" and 30 age-matched healthy subjects, not suffering from any kind of neurological disorders, as "Controls". Using a digital electromyography machine, the Latency, Amplitude and Conduction Velocities of Motor and Sensory fibres of Ulnar and Median nerves were recorded. The results were compared among controls and cases using suitable statistical tests (descriptive statistics and significance testing using unpaired t-test). Results: In this study, with regard to Sensory Nerve conduction Velocity (SNCV), statistically very significant difference was noted in case of right (p 0.0011) and left (p 0.0037) ulnar nerves among controls and cases. The difference in the amplitude of Motor Action potential (MAP) with regard to right median nerve, among cases and controls, was also statistically significant (p 0.0127). Further the amplitude of Sensory Nerve Action Potential (SNAP) values were higher among cases compared to controls. Conclusions: As such, the findings of this study (and which is also corroborated by many previous studies) lead us to the conclusion that NCV studies can detect lepromatous neuropathy much before the emergence of frank clinical signs and this type of neuropathy is predominantly demyelinating in nature with occasional axonal loss.